Prospective evaluation of complications associated with orthosis and prosthesis use in canine patients - Rosen, Sydney; Duerr, Felix Michael; Elam, Lindsay Hochman (Frontiers in Veterinary Science, 2022)
The primary objective of this study was to prospectively determine complications and outcomes associated with custom orthosis and prosthesis use in the canine patient. This was a prospective, clinical trial that followed patients for 12 months following device fitting. Owner-perceived complications, clinical metrology instruments, and objective gait analysis were used as outcome measures at various time points. Patients were grouped into four major categories: patients with a carpal orthosis, patients with a stifle orthosis, patients with a tarsal orthosis, and patients with a prosthetic device. Forty-three patients were included in the study. Thirty-nine out of 43 patients (91%) experienced at least one complication, with 7/7 (100%) prosthesis patients experiencing at least one complication. At least one skin complication was reported for the following patient groups during the first three months of use: 8/14 (58%) stifle orthoses, 9/10 (90%) carpal orthoses, 6/10 (60%) tarsal orthoses, and 4/7 (58%) prostheses. Patient nonacceptance of the device was identified in 2/15 (14%) stifle orthoses, 1/10 (10%) tarsal orthoses, and 4/7 (55%) prostheses. One out of 15 (7%) stifle orthoses, 4/10 (40%) carpal orthoses, 4/10 (40%) tarsal orthoses, and 1/7 (15%) prostheses experienced mechanical device problems necessitating repair. The majority of patients with carpal and stifle orthoses showed improvement on objective gait analysis in percent body weight distribution of the affected limb between baseline and most recent follow up without the device donned: 83% (n=6) of patients with carpal orthoses, 100% (n=11) of patients with stifle orthoses. None of the patients with tarsal orthoses showed a similar improvement (0%; n=4). Three major complications associated with canine orthosis and prosthesis use were identified in this study: skin complications (abrasions, loss of hair, sores), mechanical device problems, and patient nonacceptance of the device. Owners should be notified of these potential complications prior to pursuing orthoses or prostheses as a potential treatment option. Although clinical improvement was noted in the majority of patients with stifle and carpal pathology, given the lack of a control group, it is unknown how much of this improvement can be attributed to the orthoses.